Rediscovery of the rare Phrynomedusa appendiculata (Lutz, 1925) (Anura: Phyllomedusidae) from the Atlantic Forest of southeastern Brazil - Moraes, Leandro J. C. L.; Baêta, Délio; Amaro, Renata C.; Martensen, Alexandre C.; Pavan, Dante (Zootaxa, 2022)
The genus Phrynomedusa Miranda-Ribeiro, 1923 comprises rare and little known phyllomedusid species from southern Atlantic Forest, Brazil. Phrynomedusa appendiculata (Lutz, 1925) is known from three localities since its description and considered a “lost species” because it was last sighted 51 years ago. This pervasive lack of knowledge raised a significant concern about its threat status. Here, we present the rediscovery of P. appendiculata from a breeding population in the Atlantic Plateau forests of the state of São Paulo. This new record allowed the gathering of novel ecological, acoustic and morphological data for this species. Most of the novel data agreed with the variation historically reported for the species, but we found subtle divergences that we interpret as intraspecific variation. Moreover, this record also allowed a reassessment of geographic distribution of the species, and the first inference of its phylogenetic relationships based on molecular data (mitochondrial and nuclear DNA). The resulting phylogeny corroborated the generic placement and evolutionary distinctiveness of P. appendiculata, evidencing the species as sister to the clade P. marginata + P. dryade. Based on novel and historical data, we discuss some putative factors influencing the rarity of P. appendiculata and its congeners, and provide conservation perspectives. We expect that the novel data can support further assessments of threat status for this rare species, as well as initiatives aiming its conservation.